Epidemiology of neural tube defects and folic acid - Shurtleff David B (Cerebrospinal Fluid Research, 2004)
Abstract This review article combines four disparate observations about Neural Tube Defects (NTDs). They are the worldwide decline in the birth incidence that began prior to prenatal diagnosis; family recurrence risks; the effect of prenatal diagnosis and termination of affected pregnancies; and the effect of folic acid.